The small GTPase ARF6 regulates sphingolipid homeostasis and supports proliferation in acute myeloid leukemia - Helong Gary Zhao; Nataly Cruz-Rodriguez; Kent C. Johnson; Anthony D. Pomicter; Briana Bates; Benjamin Bateman; Torsten Haferlach; Tongjun Gu; Jonathan Ahmann; Dongqing Yan; Greg S. Lee; Weiquan Zhu; et al. (Haematologica)
Metabolic dependencies are emerging as promising therapy targets in cancer, including acute myeloid leukemia (AML). Several metabolic vulnerabilities have been identified in AML cells, including a requirement for balanced sphingolipid metabolism to maintain survival and proliferation. Here we describe a novel function of the RAS superfamily small GTPase ARF6 in maintaining sphingolipid homeostasis in AML. Genetic depletion of ARF6 inhibited the proliferation of AML cell lines and reduced colony formation of primary AML CD34+ cells. Mechanistically, ARF6 promotes conversion of ceramide to sphingomyelin by enhancing sphingomyelin synthase (SGMS1/2) expression, thereby preventing accumulation of cytotoxic ceramide levels. Accordingly, higher expression of ARF6 and its effectors SGMS1/2 in AML patient cells correlates with shorter survival in two independent AML cohorts, with ARF6 exhibiting an adverse prognostic effect independent of European Leukemia Net genetic risk. Small molecule inhibitors of ARF6 suppressed colony formation by primary AML CD34+ cells, but not cord blood CD34+ cells and showed activity in xenograft models. The dependency of AML cells on ARF6 to regulate sphingolipid homeostasis may present a therapeutic opportunity.